Pediatric medicolegal autopsy in France: A forensic histopathological approach. (January 2018) - Delteil, Clémence; Tuchtan, Lucile; Torrents, Julia; Capuani, Caroline; Piercecchi-Marti, Marie-Dominique
Abstract: The aim of postmortem medicolegal examination in pediatric death is primarily to establish the circumstances and causes of death and to exclude child abuse. In France, pediatric death is systematically documented by medicolegal or medical autopsy. In case of medicolegal autopsy, the complementary examinations, requested and financed by justice, are rarely limited to a histopathological examination. However in medical autopsies other tools are available to the pathologist as toxicology, biochemistry and molecular biology. The purpose of this article is to evaluate the efficacy of forensic histopathology in pediatric forensic autopsies. We analyze the main causes of pediatric death in a forensic context. Between 2004 and 2015, 157 infant deaths were identified in Marseille university hospital. The forensic histopathology and autopsy reports of all 157 cases were available for systematic review. Medical or surgical causes represented 41, 3% of deaths in our center, accidental causes 8.1% and child abuse 28, 8%. The definitive diagnosis was made at autopsy in 30% of cases and at histopathological examination in 70% highlighting that forensic histopathology is an indispensable tool in pediatric medicolegal autopsies. Significant histological abnormalities may be detected in selected organs such as the brain, lungs, heart, liver, adrenal glands and kidneys in spite of macroscopically normal appearances. This justifies systematic sampling of all organs. Despite the implementation of the French sudden infant death protocol which recommends medical autopsies, too many pediatric autopsies are carried out in a medicolegal context. 30% of the cases remain without diagnosis at the end of the autopsy and histological examination. This number could be reduced by the contribution of others laboratory investigation. Highlights: Significant histological anomalies are seen in macroscopically normal organs. Despite SIDS protocol, many SIDS autopsies are carried out in a medicolegal context. Natural disease accounted for about 50% of medico-legal autopsy. In France, accidental deaths accounted for 8.1% of medico-legal autopsy. Child abuse was diagnosed in 31.6% of medico-legal autopsy.